Operation performance of a ground source heat pump system in the mediterranean climate zone. First results - Christodoulides, Paul; Christou, Christakis; Aresti, Lazaros; Stylianou, Iosifina I.; Florides, Georgios A. (My University, 2025)
This paper presents the configuration and performance of a Low Enthalpy Geothermal System successfully installed and utilized in the Mediterranean climate zone. Additionally, it examines the performance of different types of Ground Heat Exchangers (GHE), all installed in the same System. The Ground Source Heat Pump (GSHP) of the system consists of vertical ground heat exchangers (GHEs) in five different configurations, one double helicoidal coil in a well and an open loop (well) system. The entire system is constantly monitored by a Building Management System (BMS) that records the energy, volume flow, incoming and outgoing temperature at critical points of the system. Based on the recorded values, the performance of the System was analyzed in a heating and a cooling working mode, after examining the power flows in and out from critical points of the System. Results show higher heat exchange values inside the open well, both in heating and cooling mode suggesting the usage of this type of GHE, where applicable. Additionally, the electric power consumed by the chillers which are the largest electricity consumers within the System, is approximately five times lower than the power placed in the building by the Geothermal System (SCOP between 4.5 and 5). In terms of primary energy savings, we can say with confidence the GSHP systems working under Mediterranean climate zone conditions, can be consider as high efficiency solutions, verifying the theoretical efficiency given by the manufacturer of the GSHP.
Keywords: Geoengineering